Hemoglobin measured by Hemocue and a reference method in venous and capillary blood: a validation study - Neufeld Lynnette; García-Guerra Armando; Sánchez-Francia Domingo; Newton-Sánchez Oscar; Ramírez-Villalobos María Dolores; Rivera-Dommarco Juan (Instituto Nacional de Salud Pública, 2002)
Objective. To assess the comparability of hemoglobin concentration (Hb) in venous and capillary blood measured by Hemocue and an automated spectrophotometer (Celldyn) and to document the influence of type of blood (capillary or venous) and analysis method on anemia prevalence estimates. Material and Methods. Between February and May 2000, capillary and venous samples were collected from 72 adults and children at Hospital del Niño Morelense (Morelos State Children's Hospital) in Cuernavaca, Morelos, Mexico, and assessed for Hb using the Hemocue and Celldyn methods. Estimated Hb levels were compared using the concordance correlation coefficient and Student's t test for paired data. The sensitivity and specificity for anemia diagnosis were estimated and compared between type of blood and method of assessment. Results. Capillary blood had higher Hb (+0.5g/dl) than venous blood in adults and children, as did samples assessed by Celldyn compared to Hemocue (+0.3g/dl). Specificity to detect anemia was adequate (>0.90) but sensitivity was low for capillary blood assessed by Hemocue (<0.80). Conclusions. The difference in Hb between venous and capillary blood is likely related to biological variability. Hemoglobin concentration in capillary blood assessed by Hemocue provides an adequate estimation of population anemia prevalence but may result in excess false negative diagnoses among individuals. The results of this study stress the importance of sample collection technique, particularly for children. Method of analysis and sampling site need to be taken into consideration in field studies.